Análise comparativa de geração entre tecnologia de microinversores e inversor string em um sistema fotovoltaico conectado à rede localizado em Fortaleza/CE - Feitosa, Davi (2022)
Considering the increase in electricity consumption, the constant readjustments in energy tariffs and the search for the expansion of the Brazilian energy matrix, photovoltaic generation (PV) appears as an alternative for this expansion, gaining more and more notoriety over the last few years. The present work carried out a case and comparative study of the electrical generation of a PV system connected to the grid, using microinverters and string inverter. The study began with a brief review of the technical concepts that contribute to the understanding of the subject, such as the functioning of the PV system, the elements that compose it, such as PV modules, inverter, string box and bidirectional meter, in addition, a presentation sector regulation, such as Normative Resolution No. 482/2012 and Federal Law No. 14,300/2022. Of an exploratory and analytical nature, the case study proceeded from the analysis of the results of the generation of the system that is already operating with microinverters in the locality of Fortaleza-CE, from there, PVsyst and Sketchup were used. as software to carry out the simulation in the same place, using the string inverter technology, where it was possible to obtain the generation data. With the results obtained, it was possible to conclude that the technology with microinverters is the one that best meets the needs of the place, due to the particularities of the place that will be presented next. With this, it was possible to ensure better electricity generation throughout 2021, as a result of this higher generation, the choice of technology with microinverters generated financial savings for the customer, relating generation and value of the Enel/CE tariff. With technological advances and the constant emergence of new equipment, a detailed analysis of the site and an understanding of all the technical aspects of the equipment are essential, so that the application is correct, extracting the maximum yield and avoiding technical and financial losses. for the consumer